In vitro sterilization technique on embryo of black Toraja rice. (May 2018) - Haring, F; Riadi, M; Rafiuddin,; Sjahril, R; Muchlis, A R
Abstract: Toraja black rice has a high anthocyanin content, a water-soluble pigments, with antioxidant activity. Toraja black rice has a variety of seeds colour in one panicles such as full black (the outside and inside the rice), medium black (the outside and slightly inside rice) and a little black (only the outside of rice). Embryo culture in vitro is one way to grow plants in sterile conditions. The presence of contamination and the death of the embryo require in vitro embryo culture. The sterilization technique is a very important first step to eliminate contamination and the death of embryos. This research aims to determine the right material composition for sterilization of black rice's embryo. The experiment was done by growing black rice on half strength MS media with the treatment of three method of sterilization, i.e .: S1 (70% alcohol for 5 minutes, 3% and 2% Chlorox each for 10 minutes, ), S2 (70% alcohol for 3 minutes, 2% Clorox for 10 minutes) and S3 (70% alcohol for 3 minutes and 1% Clorox for 15 minutes). The materials used are rice seedlings that have been cut in two and opened the pericarp of paddy grain, leaving a piece of rice that has a complete embryo. The best sterilization for Toraja black rice embryo culture was using the S3 composition. Best germination was seen on the seeds with full and medium black color.